Two cases of cisplatin-induced permanent renal failure following neoadjuvant chemotherapy for esophageal cancer. (2016) - Sasaki, Tomohiko; Motoyama, Satoru; Komatsuda, Atsushi; Shibata, Hiroyuki; Sato, Yusuke; Yoshino, Kei; Wakita, Akiyuki; Saito, Hajime; Anbai, Akira; Jin, Mario; Minamiya, Yoshihiro
Highlights: Two esophageal cancer patients developed severe acute renal failure after neoadjuvant chemotherapy with cisplatin and 5-fluorourasil. Volume expansion remains the most effective strategy for prevention of cisplatin nephrotoxicity. The two patients described here received sufficient drip infusion and produced good urine volumes. In both cases, renal biopsy examination indicated partial recovery of the proximal tubule, but renal function did not recover. Abstract: Introduction: We experienced two esophageal cancer patients who developed severe acute renal failure after neoadjuvant chemotherapy with cisplatin and 5-fluorourasil. Presentation of case: After administration of cisplatin, their serum creatinine increased gradually until they required hemodialysis and their renal failure was permanent. In both cases, renal biopsy examination indicated partial recovery of the proximal tubule, but renal function did not recover. After these events, one patient underwent definitive radiotherapy and the other underwent esophagectomy for their esophageal cancers, while continuing dialysis. Both patients are alive without cancer recurrence. Discussion: In these two cases of cisplatin-induced renal failure, renal biopsy examination showed only slight disorder of proximal tubules and tendency to recover. Conclusion: Although cisplatin-related nephrotoxicity is a well-recognized complication, there have been few reports of renal failure requiring hemodialysis in cancer patients. In this report, we present their clinical courses and the pathological findings of cisplatin-related renal failure.